The effects of transcutaneous electrical nerve stimulation during the first stage of labor: a randomized controlled trial - Anne Njogu; Si Qin; Yujie Chen; Lizhen Hu; Yang Luo (BMC, 2021)
Abstract Background Labor pain during childbirth can have devastating effects on the progress of labor, mother, and fetus. Consequently, the management of labor pain is crucial for the well-being of the mother and fetus. Transcutaneous electrical nerve stimulation (TENS) is a non -pharmacological analgesic technique. It uses a low-voltage electrical current to activate descending inhibitory systems in the central nervous system to relieve pain. This study aimed to determine the effects of TENS therapy in the first stage of labor. Methods In this single-blind randomized controlled trial, we screened low-risk pregnant women who anticipated spontaneous vaginal delivery. Women were assigned (1:1) to either the experimental group (received TENS therapy in the first stage of labor) or the control group (received routine obstetric care). The women, midwives, and researchers working in the gynecology and obstetric department were aware of the treatment group, but statisticians analysis the data were blinded. The primary outcome was labor pain intensity, assessed by visual analog scale (VAS) immediately after the randomization, at 30, 60, and 120 min after TENS therapy, and 2-24 h post-delivery. We used SPSS 21.0 software in data analysis. An independent sample t-test compared the mean VAS scores and labor duration between groups. A Chi-square test was employed to compare categorical variables between the groups. A significant level of ≤0.05 was statistically significant. Results A total of 326 pregnant women were eligible: experimental group (n = 161) and control group (n = 165). The experimental group had statistically significantly lower mean VAS scores at a different time (30, 60, and 120 min post-intervention and 2-24 h post-delivery) than the control group (p < 0.001). The experimental group demonstrated a statistically significant shorter duration of the active labor phase than the control group (p < 0.001). Conclusion This study indicates that TENS can be used as a non-pharmacological therapy to reduce pain and shorten the active labor phase. Trial registration ISRCTN registry, ISRCTN23857995 . Registered on 11/12/2020, 'retrospectively registered.